Assessing hypoxic damage to placental trophoblasts by measuring membrane viscosity of extracellular vesicles. (April 2022) - Huang, Changjin; Li, Hui; Powell, Juliana S.; Ouyang, Yingshi; Wendell, Stacy G.; Suresh, Subra; Hsia, K. Jimmy; Sadovsky, Yoel; Quinn, David
Abstract: Introduction: As highly sophisticated intercellular communication vehicles in biological systems, extracellular vesicles (EVs) have been investigated as both promising liquid biopsy-based disease biomarkers and drug delivery carriers. Despite tremendous progress in understanding their biological and physiological functions, mechanical characterization of these nanoscale entities remains challenging due to the limited availability of proper techniques. Especially, whether damage to parental cells can be reflected by the mechanical properties of their EVs remains unknown. Methods: In this study, we characterized membrane viscosities of different types of EVs collected from primary human trophoblasts (PHTs), including apoptotic bodies, microvesicles and small extracellular vesicles, using fluorescence lifetime imaging microscopy (FLIM). The biochemical origin of EV membrane viscosity was examined by analyzing their phospholipid composition, using mass spectrometry. Results: We found that different EV types derived from the same cell type exhibit different membrane viscosities. The measured membrane viscosity values are well supported by the lipidomic analysis of the phospholipid compositions. We further demonstrate that the membrane viscosity of microvesicles can faithfully reveal hypoxic injury of the human trophoblasts. More specifically, the membrane of PHT microvesicles released under hypoxic condition is less viscous than its counterpart under standard culture condition, which is supported by the reduction in the phosphatidylethanolamine-to-phosphatidylcholine ratio in PHT microvesicles. Discussion: Our study suggests that biophysical properties of released trophoblastic microvesicles can reflect cell health. Characterizing EV's membrane viscosity may pave the way for the development of new EV-based clinical applications. Graphical abstract: Image 1 Highlights: Fluorescence lifetime measurements enable EV membrane viscosity characterization. Different types of EVs secreted from PHTs feature distinctive phospholipid compositions. Hypoxia induces reduction in PE-to-PC ratio in PHT microvesicles. Changes in microvesicle membrane viscosity faithfully reveal hypoxic injury to PHTs.